Ecofeminism and Process Philosophy - Christ, Carol P. (Feminist theology, 2006)
In this article Carol Christ illustrates the ways in which process philosophy offers dynamic alternatives to dualistic habits of thought. She highlights how the Goddess is the most relational in the process and therefore the most sympathetic to the unfolding of the universe and those who inhabit it, human and non-human alike. Change she asserts is good, indeed divine, a statement in bold contrast to the Western tradition which attempts to fix and control all things. The individual and her relationship to the environment becomes an active process, with neither reduced to mere things, and both ever changing in relationship. The article offers a resounding challenge to those still stuck in dualistic metaphysics and the world that springs from them.